Peran Orang Tua Dalam Menjaga Kesehatan Gigi Pada Anak Prasekolah Usia 3-6 Tahun Di RT 003 RW 001 Dusun Sumberbendo Desa Sumberbendo Kecamatan Pare Kabupaten Kediri (STIKES dan AKZI Karya Husada Kediri, 2023)
Dental and oral health is a part of body health that cannot be separated from one another. Various dental and oral diseases that occur in most children are health problems that really need special attention. In this case, parents play an important role in maintaining the health of their children's teeth to prevent tooth decay, such as managing their child's routine of brushing their teeth and providing food made from natural ingredients, fruits and vegetables that contain vitamins and minerals. The purpose of this study was to determine the Role of Parents in Maintaining Dental Health in Preschool Children Aged 3-6 Years. The research design is descriptive, the population and sample are 24 respondents, with total sampling technique, the instrument uses a questionnaire. The research was conducted on March 16 - April 8 2023. The single variable, namely the role of parents in maintaining dental health in preschool children aged 3-6 years, was analyzed using the proportion formula and interpreted quantitatively. The results of the study from 24 respondents showed that half of the respondents had an adequate role in maintaining the dental health of preschoolers aged 3-6 years by 12 respondents (50%), almost half of the respondents had a less role as many as 7 respondents (29%) and a small portion of the respondents have a good role as much as 5 respondents (21%). The role of parents in maintaining the dental health of preschoolers aged 3-6 years is influenced by gender, education, information, occupation, and income of the respondents. It is hoped that parents will always increase their knowledge and spend a lot of time for their children in managing their children's teeth brushing routines, in order to maintain the dental health of preschool children aged 3-6 years.